Spontaneous Staphylococcal Cassette Chromosome mec Element Excision in Staphylococcus aureus Nasal Carriers - Boundy, Sam (American Society for Microbiology, 2012)
Among 23 patients carrying methicillin-resistant Staphylococcus aureus (MRSA) in their anterior nares, 6 (26%) also carried methicillin-susceptible S. aureus (MSSA) as less prevalent flora. In 4 of the 6 patients, the MSSA was unrelated to prevalent MRSA, as determined by pulsed-field gel electrophoresis (PFGE), multilocus sequence typing (MLST), and staphylococcal protein A (spa) typing. However, in two patients, the strains were identical except for the absence of spontaneous staphylococcal cassette chromosome mec (SCCmec). We consider this evidence of spontaneous SCCmec excision in vivo.